Longer-term health and social care strategies for stroke survivors and their carers: the LoTS2Care research programme including cluster feasibility RCT - Anne Forster; Seline Ozer; Thomas F Crocker; Allan House; Jenny Hewison; Elaine Roberts; Josie Dickerson; Gill Carter; Claire Hulme; Matthew Fay; Gillian Richardson; Alan Wright; et al. (NIHR Journals Library, 2021)
Background: It is reported that the longer-term outcomes for stroke survivors are poor, with a range of unmet needs identified. Objectives: The aims were to develop and test a longer-term stroke care strategy focused on improving the quality of life of stroke survivors and their carers by addressing unmet needs, and maintenance and enhancement of participation (i.e. involvement in life situations). Design: Five overlapping workstreams were undertaken - (1) refinement of content by semistructured interviews with stroke survivors and their carers and by a review of the literature to inform content and delivery of the care strategy; (2) exploration of service models by national survey and focus groups with purposely selected services; (3) intervention development by interaction with a reference group of stroke survivors, carers, and health and social care professionals; (4) refinement and pilot implementation of the developed intervention in three stroke services (case studies); and (5) a cluster randomised controlled feasibility trial in 10 stroke services across England and Wales. Setting: The intervention development work and feasibility trial were in stroke services (inclusive of primary, secondary, community and social care provision) across England and Wales. Participants: Participants were stroke survivors resident in the community and their carers, and health and social care professionals in the included stroke services. Data sources: Interviews with 28 stroke survivors and their carers at least 9 months post stroke ascertained their needs and the barriers to and facilitators of addressing those needs. Additional literature reviews identified 23 needs. No evidence-based interventions to address these needs were reported; self-management was highlighted as a possible delivery mechanism. In workstream 2, a national survey revealed that the most common model of stroke service provision was care up to 12 months post stroke, reported by 46 (40%) services. Thirty-five (30%) services provided care up to 6 months post stroke and 35 (30%) provided care beyond 12 months, thus identifying 6 months post stroke as an appropriate delivery point for a new intervention. Through focus groups in a range of services, stroke survivors' perceived unmet needs and the barriers to and enablers of service provision were identified. Intervention: Using information obtained in workstreams 1 and 2 and working closely with a stakeholder reference group, we developed an intervention based on the unmet needs prioritised by stroke survivors and their carers (workstream 3). In workstream 4, action groups (clinicians, stroke survivors and researchers) were established in three stroke services that led implementation in their service and contributed to the iterative refinement of the intervention, associated training programme and implementation materials. The intervention (called New Start) was delivered at 6 months post stroke. Key components were problem-solving self-management with survivors and carers, help with obtaining usable information, and helping survivors and their carers build sustainable, flexible support networks. Results: A cluster randomised feasibility trial (workstream 5) was successfully implemented in 10 stroke services across England and Wales, with associated process and health economic evaluations. Five services were randomised to provide New Start, while five continued with usual care; 269 participants were recruited. Progression criteria - in terms of our pre-determined (red, amber, green) criteria for progress to a full trial: target stroke survivor recruitment rates were achieved, on average, across sites (24.1 per site over 6 months, green); 216 (80.3%) registered stroke survivors returned follow-up questionnaires at 9 months (84.1% in the intervention arm and 75.8% in the usual care arm, green); according to data reported by sites, overall, 95.2% of registered stroke survivors were offered at least one session of the intervention (green); all five intervention sites had at least two facilitators deemed competent, delivered the New Start intervention and provided it to stroke survivors (green). However, at some sites, there were concerns regarding the number of stroke survivors being offered, accepting and receiving the intervention. Only small differences in outcomes and costs were observed between the New Start and usual care groups, and considerable uncertainty around the cost-effectiveness remains. Conclusions: We report a complex programme of work that has described the longer-term needs of stroke survivors and highlighted evidence and service gaps. Working closely with stroke survivors, an intervention was developed that has been refined in three services and feasibility tested in a cluster randomised controlled trial. Further refinement of the target population and optimisation of the intervention materials is required prior to a full randomised controlled trial evaluation. Future work: Optimisation of the intervention, and clearer specification of recipients, are required prior to a full trial evaluation. Trial registration: Current Controlled Trials ISRCTN38920246. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 9, No. 3. See the NIHR Journals Library website for further project information.